Meningkatkan Kemampuan Literasi Numerasi Siswa pada Pembelajaran IPA melalui Metode Problem Solving di Sekolah Dasar - Isa, Vika Notalia; Pramulia, Fuji; Juita, Roja; Syahira, Fizna; Harliyani, Wiwin; Metriani, Leoni Putri (TSAQOFAH, 2023)
This study aims to improve students' numeracy literacy in science subjects using the problem solving method. This type of research is classroom action research (CAR). This research was conducted in class V with a total of 4 male students and 6 female students. This research consisted of two cycles and each cycle held two meetings. Data collection techniques using observation techniques, and documentation. The results showed that there was an increase in students' numeracy literacy in science subjects using the problem solving method from cycle I to cycle II. An increase in student numeracy literacy occurs because using problem solving methods or problem solving methods can make children active and enthusiastic in learning, not just monotonous and boring. Then the results of the assessment of science numeracy literacy learning increased. This can be seen from the number of students whose grades are above the minimum completeness criteria. The percentage of numeracy literacy skills in science subjects in cycle II increased from 43.75% in the inappropriate category to 81.25% in the appropriate category in the 2022/2023 school year.